Glacial geomorphology of Teesdale, northern Pennines, England: Implications for upland styles of ice stream operation and deglaciation in the British-Irish Ice Sheet. Issue 6 (December 2018) - Evans, David J.A.; Dinnage, Matthew; Roberts, David H.
Abstract: The glacial geomorphology of Teesdale and the North Pennines uplands is analysed in order to decipher: a) the operation of easterly flowing palaeo-ice streams in the British-Irish Ice Sheet; and b) the style of regional deglaciation. Six landform categories are: i) bedrock controlled features, including glacitectonic bedrock megablocks or 'rubble moraine'; ii) discrete mounds and hills, often of unknown composition, interpreted as weakly streamlined moraines and potential 'rubble moraine'; iii) non-streamlined drift mounds and ridges, representing lateral, frontal and inter-ice stream/interlobate moraines; iv) streamlined landforms, including drumlins of various elongation ratios and bedrock controlled lineations; v) glacifluvial outwash and depositional ridges; and vi) relict channels and valleys, related to glacial meltwater incision or meltwater re-occupation of preglacial fluvial features. Multiple tills in valley-floor drumlin exposures indicate that the subglacial bedform record is a blend of flow directions typical of areas of discontinuous till cover and extensive bedrock erosional landforms. Arcuate assemblages of partially streamlined drift mounds are likely to be glacially overridden latero-frontal moraines related to phases of "average glacial conditions" (palimpsests). Deglacial oscillations of a glacier lobe in mid-Teesdale are marked by five inset assemblages of moraines and associated drift and meltwater channels, named the Glacial Lake Eggleshope, Mill Hill, Gueswick, Hayberries and Lonton stages. The Lonton stage moraines are thought to be coeval with bedrock-cored moraines in the central Stainmore Gap and likely record the temporary development of cold-based or polythermal ice conditions around the margins of a plateau-based icefield during the Scottish Readvance.